(untitled) (Revista Brasileira de Pesquisa em Educação em Ciências, 2016)
The proposals of approaches that encompass the science, technology and society (STS) interactions have been shown as an alternative to aid the teaching of science to promote the Scientific and Technological Literacy (STL). Through this perspective, we developed a STS thematic approach in the discipline of Chemistry in a secondary school classroom of a public school in the metropolitan region of Curitiba-Brazil. The didactic and pedagogic intervention has been built from a series of STL parameters linked to the Indoor Air Quality (IAQ) topic and with specific contents of the discipline. We adopted a qualitative research methodology, with an interpretative approach, and we analyzed the gathered data using the Discursive Textual Analysis based on the work of Moraes and Galiazzi (2007). Data analysis shows that the development of the proposed intervention helped the students to be aware of the links between the addressed knowledge and their life context, supporting the understanding of the scientific content explored. Furthermore, we observed an increased interest and participation of the students during classes, followed by reflections of the nature of science, technology, and the multiple relationships between the scientific and technological context and the social environment.